Using 5 consecutive years of NICE guidance to describe the characteristics and influencing factors on the economic evaluation of orphan oncology drugs - Shengnan, Duan; Zixuan, Lv; Na, Zhou; Weikai, Zhu; Yuanyuan, Yi; Jiasu, Liu; Ni, Yuan (Frontiers in Public Health, 2022)
Objective: Orphan oncology drugs used in this article which were defined by the type of disease treated by drugs, as drugs used to treat rare diseases with a prevalence ≤500 per million people per year. In this article, our concern was to explore focuses on the economic evaluation of National Institute for Health and Care Excellence (NICE), when orphan oncology drugs were appraised for reimbursement, and provide advice and suggestions to decision makers. Methods: A retrospective study were used in this study. 30 guidance were gathered as our subject by NICE from 2016 to 2020, excluded drugs were not identified as orphan by EMA and orphan drugs were not used for cancer and orphan oncology drugs were terminated at the time of data collection at NICE. Qualitative analysis, descriptive statistics, and a Fisher’s exact test were conducted. Results: Of all guidance, partitioned survival model was used most to appraise orphan oncology drugs, and every drug had a kind of commercial arrangement such as PAS, MAAs, and CAAs. End of life is an important indicator which had been defined by NICE in the methods of technology appraisal in 2013, and drugs met the criterion would be given a higher threshold of ICER. In addition, we found that potential health benefits were increasingly concerned such as drug delivery. Conclusion: In the setting of uncertain clinical and cost efficacy, orphan oncology drugs are comprehensively evaluated in multiple additional dimensions, which include life-extending benefits, and innovation. NICE uses a combination of special considerations for incomplete data, appropriate economic models, and appropriate Health Technology Assessment methods during the assessment process, besides, orphan oncology drugs with insufficiency evidence were recommended CDF to afford for patients, which would obtain more availability and accessibility, based on which, high-quality drugs for treating rare cancers can fall within the scope of affordable healthcare provided by the English medical insurance fund.